The nodal response to chemoselection predicts the risk of recurrence following definitive chemoradiotherapy for pharyngeal cancer. (August 2014) - Hanai, Nobuhiro; Ozawa, Taijiro; Hirakawa, Hitoshi; Suzuki, Hidenori; Fukuda, Yujiro; Hasegawa, Yasuhisa
Abstract Conclusions: The poor response of neck tumors to induction chemotherapy (ICT) as chemoselection is related to a significantly worse prognosis, including higher risks of local recurrence and/or distant metastasis, after definitive chemoradiotherapy (CRT). Objectives: Neck dissection is frequently performed to treat residual lymph nodes after CRT for the purpose of locoregional control; however, the prognosis of patients with pathologically proven residual neck tumors is poor, and no methods for predicting unfavorable results before CRT have been established. Therefore, in the present study, we focused on the response of lymph nodes to ICT and its relationship with the prognosis among patients treated with chemoselection. Methods: We retrospectively reviewed a total of 27 oropharyngeal and 24 hypopharyngeal squamous cell carcinoma stage III/IV consecutive patients with cervical lymph node metastasis who exhibited a response of >50% in the primary tumor to ICT followed by concurrent definitive CRT. Results: The relapse-free survival of the patients who responded (partial response/complete response, PR/CR) to ICT was significantly superior to that of the patients who did not respond (stable disease, SD) to ICT (p = 0.008).